Reversible Photoswitching of Isolated Ionic Hemiindigos with Visible Light. Issue 7 (21st January 2020) - Carrascosa, Eduardo; Petermayer, Christian; Scholz, Michael S.; Bull, James N.; Dube, Henry; Bieske, Evan J.
Abstract: Indigoid chromophores have emerged as versatile molecular photoswitches, offering efficient reversible photoisomerization upon exposure to visible light. Here we report synthesis of a new class of permanently charged hemiindigos (HIs) and characterization of photochemical properties in gas phase and solution. Gas‐phase studies, which involve exposing mobility‐selected ions in a tandem ion mobility mass spectrometer to tunable wavelength laser radiation, demonstrate that the isolated HI ions are photochromic and can be reversibly photoswitched between Z and E isomers. The Z and E isomers have distinct photoisomerization response spectra with maxima separated by 40–80 nm, consistent with theoretical predictions for their absorption spectra. Solvation of the HI molecules in acetonitrile displaces the absorption bands to lower energy. Together, gas‐phase action spectroscopy and solution NMR and UV/Vis absorption spectroscopy represent a powerful approach for studying the intrinsic photochemical properties of HI molecular switches. Abstract : Charge‐tagged hemiindigo photoswitches are demonstrated to undergo reversible Z / E photoisomerization in the gas phase, proving that photoinduced structural rearrangements do not rely on a solvent but rather reflect the intrinsic characteristics of the photoswitches.